PENGARUH METODE VISIT HOME DAN POLA BIMBINGAN ORANG TUA TERHADAP MOTIVASI BELAJAR SISWA SEKOLAH DASAR DI ERA PANDEMI COVID-19 - Yusrizal Yusrizal; Baihaqi Siddik Lubis; Fatmawati Fatmawati; Delima Muzdalifah (JURNAL TEMATIK, 2020)
This study aims to know the effect of visit home methods and parental guidance patterns of student learning motivation in the pandemic era. This research was conducted at SD Negeri 060931 Medan Amplas District. The research sample was students in grade 5 which consisted of 2 classes, V-A 25 students and V-B 25 students. Research data collection using a questionnaire. Hypothesis testing is tested with two-way Anava. The results showed that: (1) There was a significant difference between the learning motivation of students who were taught using the visit home method and the learning motivation of students taught by the online method (Fcount = 23.476; sig. 0.000 <0.05). Meanwhile, the average learning motivation of students taught using the visit home method was 87.383, while the average learning motivation of students taught using the online method was 80.317; (2) The motivation to learn students who are guided by their parents intensively is higher than the motivation to learn from students who are rarely guided by their parents (Fcount = 7.673; sig. 0.008 <0.05); and (3) There is an interaction between learning methods and parental guidance patterns in influencing student learning motivation during learning in the pandemic era (Fcount = 13.003; sig. 0.000 <0.05).